How to transform urban spaces and mobility: a framework for analysing street experiments - Kinigadner, Julia; Büttner, Benjamin; Rivas de Gante, Ana; Aumann, Simone (Journal of urban design, 2024)
Street experiments have become a popular tool in urban and mobility planning and are increasingly studied in academia. Yet, systematic analysis is limited. This paper presents an assessment framework to collect information on street experiment goals, characteristics, impacts, and learnings in a systematic way. The framework is less focused, but more comprehensive than other approaches. From a scientific point of view, the systematic data collection serves as a basis to apply theoretical or analytical frameworks. From a practical point of view, the information can be used by street experiment organizers both ex-ante and ex-post, for planning, implementation, and evaluation.